Implementation of In-Depth Learning in Science Material to Train Critical Thinking Skills of High School Students in West Seram Regency - Fryan Sopacua; Venty Sopacua; Heppy Sapulete; Cicylia Triratna Kereh (Journal of Science and Science Education, 2026)
Critical thinking skills will be easily measured if through a learning approach that can make students develop a learning culture and be more contextual and meaningful. An approach that can support these critical thinking skills is the immersive learning approach. This study aims to describe the Application of Immersive Learning to Train Critical Thinking Skills of High School Students in West Seram Regency. The subjects of this study were 26 students of class XB at State Senior High School A, West Seram Regency. This study used a descriptive quantitative and qualitative research type. The research design was one group pretest-posttest design. The instruments in this study were test and non-test instruments (learning activities). The test instrument was to measure students' cognitive abilities before and after the treatment while the non-test instrument was to measure students' learning activities during the treatment. Data analysis techniques used included: qualitative descriptive analysis, namely critical thinking skills and student learning activities using the immersive learning approach. The results of the pretest and posttest showed an increase in each indicator of critical thinking skills with an average increase of all indicators above 50%. The results of learning activities showed an increase in learning activities at each meeting, so it can be concluded that the immersive learning approach can train students' critical thinking skills